Educational Ball Labyrinth Game Using Accelerometer Sensor as a Media for Introducing National Capitals in the World - Ericka Sukma Putri Wilujeng; Yulian Findawati (Universitas Muhammadiyah Sidoarjo, 2017)
Learning through games is one of the good methods to reduce the students’ boredom during teaching and learning process. The android game,a maze, displays the capital city of the world. It will be useful for the learning process. The appearance of the capital used is only limited to Asia. The name of game is Maze, a unique game loved by many phone users. The applications use free software from google, namely inventor app and as a ball mover, we use an accelerometer censor in which we move the phone to move the ball. The application is presented with different challenges such as a poin deduction when it touches the wall, the enemies can move the player to start point, the wall hurdle moves. Therefore, from those obstacles are expected to add the excitement of the game.